Green Schoolyards in Low-Income Urban Neighborhoods: Natural Spaces for Positive Youth Development Outcomes - Bates, Carolyn R.; Bohnert, Amy M.; Gerstein, Dana E. (Frontiers in Psychology, 2018)
Children from low-income families are increasingly growing up in urban areas with limited access to nature. In these environments, strategies that promote access to natural outdoor spaces, such as green schoolyards, may enhance positive youth development outcomes by promoting physical activity (PA) and prosocial behavior, as well as increasing perceptions of safety. The current study examines children’s PA and social interactions, as well as caregiver and teacher perceptions of safety, injuries, teasing/bullying, and gang activity on three newly renovated green schoolyards in low-income urban neighborhoods. A multi-method strategy, including behavioral mapping and caregiver- and teacher-reported surveys, was utilized at three time points to examine positive youth development outcomes and maintenance of effects over time. Analyses revealed that children evidenced a range of PA on the green schoolyards and demonstrated significant decreases in sedentary activity over time. The majority of children were engaged in social interactions with peers on the green schoolyards when observed. Less than 3% of interactions were negative and follow-up analyses found significant increases in positive interactions on the green schoolyards up to 24 months post renovation. Caregivers and teachers reported increased perceptions of safety, fewer injuries, less teasing/bullying, and less gang-related activity on the renovated green schoolyards in comparison to the pre-renovation schoolyards, and these effects were maintained up to 32 months post-renovation. Overall, the study suggests that green schoolyards may promote positive development outcomes among youth living in urban, low-income neighborhoods by providing natural and safe spaces for PA and prosocial behavior.